How complementarity and selection affect the relationship between ecosystem functioning and stability. Issue 6 (11th May 2021) - Wang, Shaopeng; Isbell, Forest; Deng, Wanlu; Hong, Pubin; Dee, Laura E.; Thompson, Patrick; Loreau, Michel
Abstract: The biotic mechanisms underlying ecosystem functioning and stability have been extensively—but separately—explored in the literature, making it difficult to understand the relationship between functioning and stability. In this study, we used community models to examine how complementarity and selection, the two major biodiversity mechanisms known to enhance ecosystem biomass production, affect ecosystem stability. Our analytic and simulation results show that although complementarity promotes stability, selection impairs it. The negative effects of selection on stability operate through weakening portfolio effects and selecting species that have high productivity but low tolerance to perturbations ("risk‐prone" species). In contrast, complementarity enhances stability by increasing portfolio effects and reducing the relative abundance of risk‐prone species. Consequently, ecosystem functioning and stability exhibit either a synergy, if complementarity effects prevail, or trade‐off, if selection effects prevail. Across species richness levels, ecosystem functioning and stability tend to be positively related, but negative relationships can occur when selection co‐varies with richness. Our findings provide novel insights for understanding the functioning‐stability relationship, with potential implications for both ecological research and ecosystem management.